The Impact of Globalization on the Dynamics of the Domestic Market of National Economies - Yu. S. Bogachev; S. R. Bekulova (Мир новой экономики)
In the context of the turbulence of the global economy, the relevance of research aimed at determining the ability to ensure the sustainable development of national economies within the current model of global economic development is increasing.   The purpose of this study is to obtain data characterizing the development potential of national economies.   The article analyzes the impact of globalization on the dynamics of development of the leading national economies in the ranking of countries in terms of GDP at PPP with a population of more than 50 million people. At the same time, the following characteristics were studied: labor productivity, the level of debt burden, the level of consumption of industrial products and services in the domestic market, the standard of living of the population, the ratio of income of the population and the level of per capita consumption. It is shown that in the analyzed countries the total per capita consumption is greater than per capita GDP. It was revealed that the differentiation of the debt burden in various segments of the economy is due to the difference in the dynamics of labor productivity. It is shown that within the framework of the current models of national economies, the conditions for the generation of structural problems and the decline in the level of consumption and the quality of life of the population have been formed.